2012
DOI: 10.1375/twin.15.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Nature, Nurture, and Ethnocentrism in the Minnesota Twin Study

Abstract: The preponderance of research on the study of ethnocentrism has primarily attributed such attitudes to learned behavior. The research here advances the argument that both socialization and genetic inheritance contribute to the development of ethnocentric attitudes and behavior. This analysis employs the Minnesota Twins Political Survey data consisting of 596 complete twin pairs. Using the classical twin design, we employed structural equation modeling to model the covariance of twins in regards to additive gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 8 publications
2
28
0
Order By: Relevance
“…For example, Lewis and Bates (2010) reported that in-group favoritism (identification with, and preferences for, individuals of one's own race, religion, and ethnicity) was underpinned by a common latent factor, which, in turn, was highly heritable (c. 50%). This result was recently replicated by Orey and Park (2012), who showed that ethnocentrism was significantly influenced by genetic factors, although to more modest levels (c. 20%). Of interest, neither of these studies found evidence for shared-environment effects on generalized in-group favoritism, in contrast to common conceptualizations concerning the origins of intergroup attitudes (Adorno et al, 1950), although in keeping with research on other psychological traits (Turkheimer, 2000).…”
Section: Genetic Studies Of In-group Favoritism and Norm Concernsmentioning
confidence: 67%
See 1 more Smart Citation
“…For example, Lewis and Bates (2010) reported that in-group favoritism (identification with, and preferences for, individuals of one's own race, religion, and ethnicity) was underpinned by a common latent factor, which, in turn, was highly heritable (c. 50%). This result was recently replicated by Orey and Park (2012), who showed that ethnocentrism was significantly influenced by genetic factors, although to more modest levels (c. 20%). Of interest, neither of these studies found evidence for shared-environment effects on generalized in-group favoritism, in contrast to common conceptualizations concerning the origins of intergroup attitudes (Adorno et al, 1950), although in keeping with research on other psychological traits (Turkheimer, 2000).…”
Section: Genetic Studies Of In-group Favoritism and Norm Concernsmentioning
confidence: 67%
“…While environmental factors are commonly believed to underpin in-group favoritism and out-group derogation, including parental rearing environment (Adorno, Frenkel-Brunswik, Levinson, & Sanford, 1950) or scarcity of key resources (Sherif, 1966), recent research shows that genetic factors also influence individual differences concerning in-group sentiment (Lewis & Bates, 2010;Orey & Park, 2012;Weber, Johnson, & Arceneaux, 2012). However, whether these heritable effects are specific for in-group bias or overlap with more general psychological systems is currently unclear.…”
mentioning
confidence: 99%
“…Ingroup favoritism is also highly heritable (Lewis & Bates, 2010;Orey & Park, 2012) and shares genetic links with authoritarian concerns for the maintenance of social norms (Lewis & Bates, 2014). The independence and predominance of ingroup favoritism has, to date, generally been implied through observations of differential favoring behaviors and ad-hoc or minimal intergroup settings that may underrepresent the role of outgroup hostility (Schaller, Park & Faulkner, 2003).…”
Section: Favoritism Hostility and Multiculturalismmentioning
confidence: 99%
“…Additional information is presented in Table 3. This measure of Ethnocentrism has been used in previous research and found to have construct validity (Kam and Kinder 2012;Orey and Park 2012).…”
Section: Ethnocentrismmentioning
confidence: 99%